Literasi Digital Terhadap Kesiapan dan Minat Kerja Siswa SMK Terpadu Sinar Islami - Khairunnisa, Iin; Purnamasari, Intan (FKIP Universitas Muhammadiyah Sukabumi, 2024)
This research aims to find out whether digital literacy can influence work readiness and whether digital literacy can increase vocational school students' work interest. Digital literacy is used as the independent variable (X), while work readiness is used as the dependent variable (Y1) and work interest as the dependent variable (Y2). This research uses quantitative methods. The population in this study was 52 vocational school students and the sample used was 34 vocational school students using random sampling technique. Judging from the results of the coefficient of determination test or R Square for variables X and Y1, it is 640, which is equivalent to 64.0%, and variable on the work readiness variable (Y1) and the work interest variable (Y2).